2008
DOI: 10.1111/j.1469-7580.2008.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of MG1 mucin in human bulbourethral glands

Abstract: Salivary mucins MG1 and MG2 have been found in the oral cavity where they perform several functions such as the formation of the mucous layer covering the oral mucosa and teeth. Recent studies have demonstrated their presence in other organs and tissues. The aim of this study was to determine their expression in human bulbourethral (Cowper's) glands. Normal bulbourethral glands were obtained at surgery and fixed in a mixture of 1% paraformaldehyde-1.25% glutaraldehyde in 0.1 M cacodylate buffer and embedded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…We find comparable results in mice, except for expression of Muc5b transcripts in epididymis. The recent results of Piludu et al (2009) suggest that MUC5B glycoproteins are probably contributed by bulbourethral glands, a tissue not tested by Russo et al (2006). Piludu et al (2009) localized anti-MG1 reactivity to bulbourethral mucous cells.…”
Section: Discussionmentioning
confidence: 98%
“…We find comparable results in mice, except for expression of Muc5b transcripts in epididymis. The recent results of Piludu et al (2009) suggest that MUC5B glycoproteins are probably contributed by bulbourethral glands, a tissue not tested by Russo et al (2006). Piludu et al (2009) localized anti-MG1 reactivity to bulbourethral mucous cells.…”
Section: Discussionmentioning
confidence: 98%
“…Mucins are highly glycosylated proteins involved with mucosal innate immune response (53,54). Specifically, mucin-5B is a high-molecular-weight, gel-forming protein (55). Russo et al (56) were the first to demonstrate the presence of mucin-5B in the seminal plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Russo et al (56) were the first to demonstrate the presence of mucin-5B in the seminal plasma. Thereafter, Piludu et al (55) demonstrated that this protein is secreted by the bulbourethral glands, where it seems to protect the epithelium against infection. The function of mucin-5B in semen remains unknown, but it is suggested that it might modulate sperm transport in the male and female reproductive tracts (55,57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since analysis of prostate cancer-specific molecules in urine, such as PCA3, often requires normalization to KLK3 mRNA to account for the sample dilution 13 , we also investigated if normalization of protein concentrations by total KLK3 protein in SP would improve the performance of markers ( Figure 5). Levels of MUC5B, a mucin exclusively expressed and secreted by the Cowper's glands 50 , were significantly lower in PCa (0.4-fold change, P =0.005) before, but not after normalization by KLK3. Due to its exclusive expression in the Cowper's glands and its potentially high variability in SP, MUC5B thus was not considered as a candidate.…”
Section: Upgrade Of the Srm Assay For The Validation Phasementioning
confidence: 95%